First Total Synthesis of Lippialactone and Its C9 Epimer - Radha Krishna, Palakodety; Nomula, Rajesh; Kunde, Ramesh (Synthesis, 2014)
This paper describes the first total synthesis of bioactive lippialactone and C9-epi-lippialactone adopting Keck asymmetric allylation/Barbier allylation and olefin cross-metathesis as the key steps.
Keywords: lippialactone; 6-substituted α,β-unsaturated δ-lactones; l-threonine; Keck allylation; Barbier allylation; cross-metathesis